Fingerprint inventory smart students at SMA N 1 Gunung Tuleh Pasaman Barat - Ainil Putri; Yelida, B. (Genetikawan Muda Indonesia, 2024)
Fingerprints are one of the biological characteristics possessed by humans. Fingerprints consist of arch, whorl and loop pattern types. The average human has a fingerprint pattern. One individual and another individual have different fingerprint patterns and are each unique. This research method uses a descriptive method with a purposive sampling technique which was carried out by taking fingerprint samples from students who were ranked 1 to 10 from class phase f and class XII at SMA N 1 Gunung Tuleh, West Pasaman district. With a sample size of 112 people. The results of the research can be concluded that the most frequently found fingerprint patterns are loop pattern fingerprints at 71.87%, then whorl finger scale patterns at 24.48%, and arch patterns at 24.48%.